2006
DOI: 10.1243/09544062jmes237
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent intraoral drug delivery microsystem

Abstract: The authors report on the concept and development of an intelligent intraoral drug delivery microsystem, that provides an alternative approach for the treatment of addiction and chronic diseases. The drug delivery system (DDS) comprises a medication replacement reservoir, a medication release mechanism, a built-in intelligence, a remote control, microsensors, and microactuators. It is thus able to release the medication in a controlled manner according to the patient needs. The emphasis of this article is on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Many groups have also used osmotic mechanisms to drive flows in microfluidic systems , Velten et al 2006, Good et al 2007, Xu et al 2010. Jensen et al (2009Jensen et al ( , 2011 appear to be the first to have connected this strategy to the Münch hypothesis.…”
Section: Synthetic Mimics Of Transport Processes In Plantsmentioning
confidence: 99%
“…Many groups have also used osmotic mechanisms to drive flows in microfluidic systems , Velten et al 2006, Good et al 2007, Xu et al 2010. Jensen et al (2009Jensen et al ( , 2011 appear to be the first to have connected this strategy to the Münch hypothesis.…”
Section: Synthetic Mimics Of Transport Processes In Plantsmentioning
confidence: 99%
“…Due to the presence of a large sugar source reservoir, this bioinspired osmotic pump can run at steady-state for several hours or more, allowing precise measurements of the physicochemical coupling at the system scale. It may also provide new strategies for pumping microscale flows in lab-on-a-chip applications (20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Fouling, being the accumulation of undesired contaminants such as organic molecules, cells, and microparticles on a submerged surface, forms a problem for many applications. [1,2] One example of mentioned previously is aligned in a regular patten, which can limit the self-cleaning capabilities. In particular, it was found that when the particle sizes are close to the cilia pitch (the spacing of adjacent cilia), the cleaning effectiveness is reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Fouling, being the accumulation of undesired contaminants such as organic molecules, cells, and microparticles on a submerged surface, forms a problem for many applications. [ 1,2 ] One example of such an application is lab‐on‐a‐chip devices, as the absorption of microparticles, cells of molecules to the device walls, or the accumulation of these contaminants in microfluidic channels, inhibits normal device operation, for example, causing microchannel clogging. [ 3 ] Another example are submerged sensor surfaces for environmental monitoring in oceans, lakes, or rivers, or in chemical and food processing operations, where fouling can lead to reduced sensitivity and/or lifetime.…”
Section: Introductionmentioning
confidence: 99%